Pengaruh penerapan total quality management terhadap kualitas pelayanan prima pada aparat kelurahan di kecamatan gunungpati Semarang - Sri Wartini (LPPM STIE DHARMAPUTRA SEMARANG, 2010)
The objectives of this research are examine the influence of applying Total Qualitative Management (TQM) on the excellent service of the village chief apparatus in Gunungpati Semarang subdistrict and to examine the biggest influence of TQM dimension towards the excellent service. The TQM dimension that is searched is the orientation to the subscriber, quality orientation, empowering the employer, management’s commitment, cooperative team, the continuity of the system, educational and expermetal. The sample consists of 160 societies in Gunungpati Subdistrict Semarang. The research method uses the survey method with questioner. The examining hypothesis in multi regression The research result find that there is some influence in applying TQM on the excellent service of the apparatus in kelurahan Gunungpati subdistrict, Semarang. another examining result which is done with contrasting the dimension of educational beta value coefficient and the biggest exercising in contrast with another beta coefficient. It means that the educational dimension and exercising that influencing on the excellent service of the apparatus in kelurahan Gunungpati subdistrict, Semarang. Keywords : Total Quality Management, excellent service, educational and exercising